Vocational school students attitudes toward computer technology Marmara University sample - ÖZNAZ, DEMET; BALIKCI, MURAT; AKYURT, NURAN (E D P SCIENCES, 2016)
Rapid changes in information and information technology nowadays change the social life of the community and have become an important factor affecting the exchange and development of the institutions accordingly. The use of computer technology in all areas such as education, health, communication and banking affect business processes and methods in organizational structure and the education of technically skilled qualified individuals becoming important. The education of qualified individuals in desired qualities is closely related to their attitudes toward computer use. The target of this study was to determine among the students in health and technical programs whether there is a relationship between independent variables such as gender, area of study, use of social media tools and the attitude towards the use of computer technology.
Keywords: Vocational school students; computer use; computer attitude scale; technology use